High piezoelectricity of Eu3+-doped Pb(Mg1/3Nb2/3)O3–0.25PbTiO3 transparent ceramics. Issue 7 (27th January 2021) - Li, Kai; Sun, Enwei; Zhang, Yongcheng; Song, Zhenzhen; Qi, Xudong; Sun, Yuan; Li, Jiaming; Yang, Bin; Liu, Jian; Cao, Wenwu
Abstract : Optically transparent Eu 3+ -doped Pb(Mg1/3 Nb2/3 )O3 –0.25PbTiO3 (PMN–0.25PT:Eu 3+ ) relaxor ferroelectric ceramics with high piezoelectricity were prepared by oxygen-atmosphere sintering followed by hot-press sintering. Abstract : Optically transparent Eu 3+ -doped Pb(Mg1/3 Nb2/3 )O3 –0.25PbTiO3 (PMN–0.25PT:Eu 3+ ) relaxor ferroelectric ceramics with high piezoelectricity were prepared by oxygen-atmosphere sintering followed by hot-press sintering. A high piezoelectric charge coefficient ( d 33 = 850 pC N −1 ) and effective piezoelectric strain coefficient ( d 33 * ≈ 1520 pm V −1 ) were achieved in the 2 mol% Eu 3+ -doped PMN–0.25PT transparent ceramic. Local nanoscale domain patterns and piezoresponse of PMN–0.25PT:Eu 3+ transparent ceramics were observed and quantitatively analyzed by using piezoelectric force microscopy and the autocorrelation function method to understand the origin of the high piezoelectricity. It is found that the introduction of Eu 3+ doping will enhance the local structure heterogeneity in PMN–PT ceramics and the obtained high piezoelectric properties are related to the dynamic behavior of local nano-domains. Our result showed that doping with rare earth element Eu 3+ is an effective method for making transparent ferroelectric ceramics with enhanced piezoelectric performance, which benefits the design and development of eletro-optic devices as well as transparent sensors and ultrasound transducers.